2018
DOI: 10.1074/jbc.ra118.005421
|View full text |Cite
|
Sign up to set email alerts
|

It takes a dimer to tango: Oligomeric small heat shock proteins dissociate to capture substrate

Abstract: Small heat-shock proteins (sHsps) are ubiquitous molecular chaperones, and sHsp mutations or altered expression are linked to multiple human disease states. sHsp monomers assemble into large oligomers with dimeric substructure, and the dynamics of sHsp oligomers has led to major questions about the form that captures substrate, a critical aspect of their mechanism of action. We show here that substructural dimers of two plant dodecameric sHsps, Ta16.9 and homologous Ps18.1, are functional units in the initial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 69 publications
5
49
0
1
Order By: Relevance
“…We demonstrate that initially smaller species of Bc (predominantly monomers and dimers) bind to heat-destabilised CLIC1 oligomers. This observation validates previous suggestions, based on studying end-stage complexes, that smaller species of sHsps have high chaperone ability and therefore initially bind to misfolded proteins 18,42,43 . Interestingly, we observed that the number of complexes formed between Bc and CLIC1 increased rapidly over the first hour of incubation and reached a plateau after 4 hr.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We demonstrate that initially smaller species of Bc (predominantly monomers and dimers) bind to heat-destabilised CLIC1 oligomers. This observation validates previous suggestions, based on studying end-stage complexes, that smaller species of sHsps have high chaperone ability and therefore initially bind to misfolded proteins 18,42,43 . Interestingly, we observed that the number of complexes formed between Bc and CLIC1 increased rapidly over the first hour of incubation and reached a plateau after 4 hr.…”
Section: Discussionsupporting
confidence: 91%
“…Whilst it is well established that sHsps can form high-molecular mass complexes with misfolded clients to prevent their aggregation [12][13][14] , little is known about how these complexes are assembled. It has been postulated that smaller sHsp oligomers have enhanced chaperone activity as a result of their increased exposed hydrophobicity and, therefore, a greater affinity for misfolded and aggregation-prone proteins [15][16][17][18] ; however, others have suggested that the larger oligomers are chaperone active [19][20][21] . Thus, it remains unclear precisely how sHsps capture misfolded proteins to form the high-molecular mass sHsp-client complexes observed as a result of their chaperone action.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structures further supported that dimers were the building block of most sHSPs [36]. Dimers were proposed to be the form that captures heat-sensitive unfolding proteins [5,81]. However, heat-induced dissociation of oligomers is not a general feature of sHSPs: for example, plant Class II cytosolic sHSP [40], yeast cytosolic HSP42 [34], sugarcane chloroplast, and mitochondria sHSP [55] remained oligomeric upon heat treatment.…”
Section: Discussionmentioning
confidence: 96%
“…The oligomerization state of sHSPs can be inuenced by the changes in pH, 9 temperature 10 as well as by post-translational modications, such as phosphorylation 11 that affects their affinity to other proteins and chaperone-like activity. 12 This relationship between changes in oligomerization and chaperone-like activity has been clearly shown for the human HSPB1 and HSPB5 as well as for the yeast HSP42. [13][14][15] While the dynamics of sHSPs oligomerization and oligomers structure were analyzed in detail mainly for archaeal and eukaryotic proteins, the common features of sHSPs seem to be universal in all kingdoms of life (for an extensive review, we refer to ref.…”
Section: Introductionmentioning
confidence: 83%